Melacak Ideal Moral dalam Hadis La Yakhtubu al-Rajulu ‘Ala Khitbati Akhihi: Sebuah Telaah Ilmu Hadis - Salam, Nor (Fakultas Syariah, 2016)
Hadith (the Prophet tradition) is the source of law which occupies a central position after the Quran which serves as explanatory of the contents of the Quran. However, if the Quran has been ascertained to be qat'i both sides wurud or tsubutnya, not the case with a Hadith that still raises various problems both in the assessment of the sanad authenticity and the contains. Thus, it is not all hadith have authentic quality both the sanad nor the matan, so it is needed to do research. Another issue is no less complex in order to